Interrelation of Vitamin D, Parathyroid Hormone, Calcium and Phosphorus in Stage 3 To Stage 5 Chronic Kidney Disease: Life Sciences-Biochemistry - DSSK, Raju; G. S .R, Kedari (International Journal of Life Science and Pharma Research, 2022)
The Kidneys maintains filtration, endocrine function and excretory function. In CKD, the said functions get impaired, that leads to changes in biochemical parameters such as increased concentration of urea and creatinine. Chronic kidney disease also causes hypocalcemia, hyperkalemia, hyperphosphatemia and secondary hyperparathyroidism. The aim of the present study was to assess the interrelationship of vitamin D, Parathyroid hormone, Calcium and phosphorus in Stage 3 to Stage 5 chronic kidney disease. The study contains 180 patients in which 45 in control group and 135 will be CKD individuals with stage 3 to stage 5 each stage consisting of 45 each. In all the subjects, serum sample was estimated for blood urea, creatinine, serum calcium and serum phosphorus by using fully automatic chemistry analyzer. Serum Vitamin D and parathyroid hormone are estimated by ELISA. GFR was estimated by the MDRD formula. Data was expressed by Mean ±SD. In the present study, the mean serum calcium and Vitamin D were decreased in stage 3, stage 4 and stage 5 compared with the control and it is statistically significant. The mean phosphorus and parathyroid hormone were increased in stage 3, stage 4 and stage 5 compared with control and it is statistically significant. There was a positive correlation between vitamin D and calcium, and also between parathyroid and Phosphorus. Whereas it showed a negative correlation between vitamin D and Phosphorus and also between Parathyroid and calcium. The assessment of these parameters will be helpful in preventing future risk and also helpful in better life and outcome.